Muḥammadiyah Fact or Complete Human in the theory of “Pantheism” to Ibn ʿArabī - Mohd. Shamsuddin, Salahuddin; Lubis, Tonang (Advances in Social Sciences Research Journal, 2019)
Ibn ʿArabi thinks that Muḥammadiyah fact has some multiple names represent the last mattress of the isthmus or the absolute fiction, at the same time these multiple names represent the first mattress of the spiritual mediators in the ranking, mediating between the absolute fiction and sensual world, which is seen. Muḥammadiyah fact is not a material, but a spiritual fact, which is found in the whole universe from up to down. It had been found previously in the prophets and messengers, which embodied in the historical and physical character of Muḥammad at the end. This is a spiritual human fact, Adam was the first material representative of its physical manifestations. This is the highest Pen, which is on the top of the all spiritual and sensual assets -in term of the existence and knowledge-. This is the first Mind caused the other partial brains: Minds of the planets and humans alike. Finally, it is a spirit of Complete Human cannot be ignored by the universe anytime, which saves the universe, as its existence and rule. This spirit represents Summit of the protection, embodies in some certain persons represent the mystical esoteric State -at the Sufis generally and Ibn ʿArabi specially-.